Improving Students’ Achievement in Reading Comprehension by Applying Contextual Teaching and Learning (CTL) - Diani Syahputri; Putri Mariyati (BIRCU, 2019)
This research aims to find out the significant improvement of the students achievement in reading comprehension by applying Contextual Teaching and Learning (CTL). The subject of this research was X grade of SMK Bandung-2 at Academic Year 2017/2018. It consisted of one class with 30 students as respondents. The objective was to discover the significant improvement of the students’ achievement in reading comprehension by applying Contextual Teaching and Learning (CTL). This research was conducted by using classroom action research. The instruments of collecting data were observation sheet, and Reading tests. The research finding is shown of that there was an improvement on the students’ reading achievement on narrative text from each cycle. It was showed from the mean of pre-test which was 56.5 with persentage 0%. After CTL was applied in the first cycle, there was an improvement of the result of the students’ in reading comprehension the mean was 69.16 with persentage 33.3%. It means that there was an improvement from pre-test to post-test I was 33.3%. And for the second cycle after reflection on the first cycle, there was an improvement of students’ mean which was 85 with persentage 100%. Based on the result showed that there was an improvement after applying CTL was 66.7%. It concluded that students’ achievement in reading comprehension by applying contextual teaching and learning (CTL) improved.